Turning water from a hindrance to the promotor of preferential electrochemical nitrogen reduction - Koh, Charlynn Sher Lin (2022)
Electrochemical nitrogen reduction reaction (NRR) offers sustainable ammonia production but suffers from poor performance owing to favorable water electrolysis. Recent designs achieve better efficiency by eradicating water but do not leverage on water as a readily available NRR proton source. Herein, we design a hydrophobic oleylamine-functionalized zeolitic-imidazolate framework coated over the electrocatalyst to achieve >18% NRR efficiency in the presence of water, an approximately fourfold boost compared to that without water. Our strategy kinetically regulates water availability at the electrocatalyst surface, suppresses direct water adsorption/electrolysis, and promotes preferential nitrogen adsorption to achieve water-assisted NRR. Conversely, control systems without hydrophobic modification experience a drastic decrease in efficiencies (<3%) upon water addition. In situ surface-enhanced Raman scattering investigation reveals that our hydrophobic system's ability in suppressing water accessibility to the electrocatalyst is the key to transform water from a hindrance to an NRR promotor. Our universal design is a paradigm shift from current approaches to achieve sustainable air-to-ammonia electrosynthesis.